Maximizing the oil content in polysaccharide-based emulsion gels for the development of tissue mimicking phantoms. (15th March 2021) - Fontes-Candia, Cynthia; Lopez-Sanchez, Patricia; Ström, Anna; Martínez, Juan Carlos; Salvador, Ana; Sanz, Teresa; Trefna, Hana Dobsicek; López-Rubio, Amparo; Martínez-Sanz, Marta
Graphical abstract: Highlights: Agar- and carrageenan-based emulsion gels have potential as tissue mimicking phantoms. Agar showed greater capacity to stabilize the oil droplets, yielding more homogeneous gels. The addition of surfactants aided oil incorporation but promoted droplet coalescence. The large deformation behaviour of the gels was dominated by the gelling network. Agar gels with high oil content are more suitable for the development of fat phantoms. Abstract: Formulations based on agar and κ-carrageenan were investigated for the production of emulsion gels applicable as tissue mimicking phantoms. The effects of the polysaccharide matrix, the oil content and the presence of surfactants on the micro-/nanostructure, rheology, and mechanical and dielectric properties were investigated. Results showed a high capacity of the agar to stabilize oil droplets, producing gels with smaller (10−21 μm) and more uniform oil droplets. The addition of surfactants allowed increasing the oil content and reduced the gel strength and stiffness down to 57 % and 34 %, respectively. The permittivity and conductivity of the gels were reduced by increasing the oil content, especially in the agar gels (18.8 and 0.05 S/m, respectively), producing materials with dielectric properties similar to those of low-water content tissues. These results evidence the suitability of these polysaccharides to design a variety of tissue mimicking phantoms with a broad range of mechanical and dielectric properties.